Community Emergency Preparedness, Resident Emergency Response Capacity, and the Effectiveness of Community Epidemic Prevention and Control - Zhenzhen Shao; Haibo Ruan; Xinting Meng; Guofeng Wang (SAGE Open)
After the outbreak of the COVID-19 pandemic, the importance of the Effectiveness of Community Epidemic Prevention and Control (ECEPC) which is directly related to the safety of people’s health and the stability of the society, is highlighted under abnormal circumstances. However, researches on Community Emergency Preparedness (CEP) and ECEPC in low and middle-income countries are of different quality. This study adopted the random sampling method. 2,250 residents from 150 communities in 140 municipalities in 20 provinces in Chinese mainland participated in the cross-sectional survey on ECEPC, with 2,112 questionnaires validly returned. Data were analyzed through descriptive statistics with optimal scaling regression model to explore the influencing mechanism of CEP and Resident Emergency Response Capacity (RERC) on ECEPC. The results revealed that 74.47% of respondents thought ECEPC was relatively good, and over 40% of respondents thought emergency risk awareness, emergency mutual-aid capacity, and psychological resilience were fairly good. Both CEP and RERC had positive and significant effects on ECEPC. The impact ranking showed the importance of emergency response system drills was ranked first at 0.165. Emergency response system could be revised and improved in practical drills. The results of the study provided new recommendations for different measures to be taken in the preparation, adjustment, and improvement phases of Emergency Response System Drills, which were conducive to building a resilient community-based epidemic prevention and control system.